Efficacy and safety of levetiracetam vs. oxcarbazepine in the treatment of children with epilepsy: a systematic review and meta-analysis - Liu, Yuanyuan; Wang, Yanxu; Li, Xingzhou; Wu, Xiaomin (Frontiers in Pediatrics, 2024)
Background: Levetiracetam (LEV) and oxcarbazepine (OXC) are new antiseizure medications (ASMs). In recent years, OXC monotherapy is widely used in children with epilepsy; however, no consensus exists on applying LEV monotherapy among children with epilepsy.Objective: The present work focused on comparing the efficacy and safety of LEV and OXC monotherapy in treating children with epilepsy.Methods: We conducted a comprehensive search across multiple databases including PubMed, Cochrane Library, Embase, Web of Science, CNKI, Wanfang Database, VIP, and China Biology Medicine disc, covering studies from inception to August 26, 2023. We included randomized controlled trials (RCTs) and cohort studies evaluating the efficacy and safety of LEV and OXC monotherapy for treating epilepsy in children. We utilized Cochrane Risk of Bias Tool in RevMan 5.3 software for assessing included RCTs quality. In addition, included cohort studies quality was determined using Newcastle-Ottawa Scale (NOS). A random-effects model was utilized to summarize the results.Results: This meta-analysis included altogether 14 studies, including 893 children with epilepsy. LEV and OXC monotherapy was not statistical different among children with epilepsy in seizure-free rate (relative risk [RR] = 1.010, 95% confidence interval [CI] [0.822, 1.242], P＞0.05) and seizure frequency decrease of ≥50% compared with baseline (RR = 0.938, 95% CI [0.676, 1.301], P＞0.05). Differences in total adverse reaction rate (RR = 1.113, 95% CI [0.710, 1.744], P＞0.05) and failure rate because of serious adverse reaction (RR = 1.001, 95% CI [0.349, 2.871], P＞0.05) were not statistical different between LEV and OXC treatments among children with epilepsy. However, the effects of OXC monotherapy on thyroid among children with epilepsy was statistically correlated than that of LEV (thyroid stimulating hormone: standardized mean difference [SMD] = -0.144, 95% CI [-0.613, 0.325], P＞0.05; free thyroxine: SMD = 1.663, 95% CI [0.179, 3.147], P＜0.05).The efficacy of LEV and OXC monotherapy in treating children with epilepsy is similar.However, OXC having a more significant effect on the thyroid than that of LEV. Therefore, LEV may be safer for children with epilepsy who are predisposed to thyroid disease than OXC.